STUDY ON IMPLEMENTATION OF WAREHOUSE RECEIPT POLICY IN PEPPER COMMODITIES IN BANGKA BELITUNG ARCHIPELAGO PROVINCE - bambang ari satria (JIAP (Jurnal Ilmu Administrasi Publik), 2020)
Bangka Belitung is the largest national pepper producing area with the trademark Muntok White Pepper. In line with that, the Provincial Government of the Bangka Belitung Archipelagohas formulated the first strategic policy in Indonesia towards the warehouse receipt system on pepper commodities. The policy arose in an effort to improve the welfare of pepper farmers. This study aims to determine the implementation of the warehouse receipt system policy on pepper commodity in Bangka Belitung and the factors that influence it.This study uses qualitative research methods. This study focuses on discussing how to implement the warehouse receipt system policy in the pepper commodity in Bangka Belitung by looking at four aspects that serve as a reference in analyzing policy implementation, namely: communication, disposition, resources, and bureaucratic structure. Data collection techniques use in-depth interviews, observation and documentation techniques.The results show that the implementation of the warehouse receipt system policy on pepper commodities in the Bangka Belitung Archipelago Province was not running optimally. One of factors that affect that policy is the aspect of communication. There are still many farmers who do not get information clearly related to the warehouse receipt system. From the aspect of disposition, there is no synergy among stakeholders in running the program. From the aspect of resources, the competencies of the management team must be increased. From the aspect of bureaucratic structure, there is a split between organizational units, namely between the Bangka Belitung Archipelago Provincial Government and the Pepper Management, Development and Marketing Agency (BP3L).